2004
DOI: 10.1063/1.1688319
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the dynamics of hydrogen atom release from the radical–radical reaction of O(3P) with C3H5

Abstract: The gas-phase radical-radical reaction dynamics of O(3P) + C3H5 --> H(2S) + C3H4O was studied at an average collision energy of 6.4 kcal/mol in a crossed beam configuration. The ground-state atomic oxygen [O(3P)] and allyl radicals (C3H5) were generated by the photolysis of NO2 and the supersonic flash pyrolysis of allyl iodide, respectively. Nascent hydrogen atom products were probed by the vacuum-ultraviolet-laser induced fluorescence spectroscopy in the Lyman-alpha region centered at 121.6 nm. With the aid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
1

Year Published

2006
2006
2012
2012

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 28 publications
2
32
1
Order By: Relevance
“…Experimental Studies: The lab-made crossed-beam apparatus for investigating gas-phase reaction dynamics has been described in detail elsewhere. [1,[5][6][7][8][9][10][11][12][13][14][15][16][17] It consists of two radical-source chambers, each pumped by a 6-inch (1400 L s À1 ) baffled diffusion pump, and a scattering chamber, pumped by a 10-inch (3000 L s À1 ) baffled diffusion pump. The average base pressure in the scattering chamber was kept below 2.0 10 À6 Torr.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Experimental Studies: The lab-made crossed-beam apparatus for investigating gas-phase reaction dynamics has been described in detail elsewhere. [1,[5][6][7][8][9][10][11][12][13][14][15][16][17] It consists of two radical-source chambers, each pumped by a 6-inch (1400 L s À1 ) baffled diffusion pump, and a scattering chamber, pumped by a 10-inch (3000 L s À1 ) baffled diffusion pump. The average base pressure in the scattering chamber was kept below 2.0 10 À6 Torr.…”
Section: Methodsmentioning
confidence: 99%
“…It builds on previous gas-phase crossed-beam studies. [5][6][7][8][9][10][11][12][13][14][15][16][17] Radical-radical reaction dynamics were investigated as part of ongoing efforts to elucidate the mechanistic and dynamic attributes of the reactions of O( 3 P) with a series of prototypal alkyl radicals, such as allyl, propargyl, tert-butyl (t-C 4 H 9 ), and vinyl, and to identify the general principles that determine their reactivity and mechanisms. Some hydrocarbon species showed intrinsic stability due to resonance stabilization or hyperconjugation.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11] The complexity of the competition between bond fission and isomerization pathways is surprising for such a small system, composed of only four heavy atoms and five hydrogen atoms. Previous studies have sought to probe the product branching and dynamics of this reaction.…”
Section: Primary Photodissociation Pathways Of Epichlorohydrin and Anmentioning
confidence: 99%
“…Their RRKM analysis of the fate of the excited allyloxy radical shows a variety of possible isomerization and subsequent decomposition pathways with only minor differences in the barrier heights [17]. A crossed-beam study of Joo et al [18] provides details of the mechanism of H atom formation. In a recent communication Leonori et al [19] reported detailed mechanistic information on the acrolein channel and found evidence for one or more C-C bond-breaking channels.…”
Section: Introductionmentioning
confidence: 98%
“…Since for the allyl radical the unimolcular C-C and C-H bond fission reactions and the reaction with molecular oxygen are significantly slower than for saturated alkyl radicals [11][12][13], the reactions of allyl radicals with atoms (O, H) and other radicals (OH, alkyl) become dominant under high-temperature conditions. Several experimental and theoretical studies have been performed to determine the rate and the products of the title reaction so far [14][15][16][17][18][19]. According to these investigations the reaction allyl + O mainly proceeds via a highly energized allyloxy intermediate, which subsequently undergoes fast decomposition, in analogy to the reactions of alkyl radicals with O atoms [20][21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%